2023
DOI: 10.1177/10711007231180212
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Progressive Deltoid Ligament Sectioning on Weber B Ankle Fracture Stability

Abstract: Background: Conventionally, transsyndesmotic fibula fractures with concomitant signs of deltoid ligament injury have been considered unstable and thus treated operatively. Recent studies have indicated that partial deltoid ligament rupture is common and may allow for nonoperative treatment of stress-unstable ankles if normal tibiotalar alignment is obtained in the weightbearing position. Biomechanical support for this principle is scarce. The purpose of this study was to evaluate the biomechanical effects of g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 21 publications
1
4
0
Order By: Relevance
“… 4 However, recent biomechanical evidence suggests that Weber B fractures with a partial deltoid ligament tear but with an intact dPTTL are stable. 2 , 9 These findings are coherent with clinical studies demonstrating acceptable patient-reported and radiographic outcomes in the short and midterm after nonoperatively treating SER4a fractures, 4 - 6 , 13 and thus challenges the traditional practice of operative treatment of SER4a fractures because of potential instability. The results of the present study provide evidence that plate fixation of the fibula only improves external rotational stability, in SER4a injury models.…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“… 4 However, recent biomechanical evidence suggests that Weber B fractures with a partial deltoid ligament tear but with an intact dPTTL are stable. 2 , 9 These findings are coherent with clinical studies demonstrating acceptable patient-reported and radiographic outcomes in the short and midterm after nonoperatively treating SER4a fractures, 4 - 6 , 13 and thus challenges the traditional practice of operative treatment of SER4a fractures because of potential instability. The results of the present study provide evidence that plate fixation of the fibula only improves external rotational stability, in SER4a injury models.…”
Section: Discussionsupporting
confidence: 71%
“…A previous study demonstrated that external rotation instability already occurs to some degree in cadaver models with no medial side injury (Weber B/SER2 injury models). 2 …”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations